Preservice Teachers and the Kairos Blanket Exercise: A Narrative Inquiry (LEARNing Landscapes, 2021)
This narrative study inquired into the experiences of preservice teachers who participated in the Kairos Blanket Exercise. During research conversations, participants shared stories that demonstrated an expansion of their knowledge and awareness. Three themes emerged: the Blanket Exercise and the research conversations were spaces where participants felt safe to ask questions; some participants began to rewrite their understanding of the history of relations; and some participants began to consider how they might contribute to decolonizing. Moreover, participants enriched by the experience were more ready and able to deliver related curricular outcomes, engage reflexively, and consider allyship.
Keywords: preservice teachers; the Kairos Blanket Exercise; narrative inquiry